Advanced heterolytic H2 adsorption of K-added Ru/MgO catalysts for accelerating hydrogen storage into aromatic benzyltoluenes - Kim, Tae Wan; Jeong, Hwiram; Jo, Yeongin; Kim, Dongun; Park, Ji Hoon; Kim, Seok Ki; Suh, Young Woong (Journal of Energy Chemistry, 2022)
Herein, we report a highly active K-added Ru/MgO catalyst for hydrogen storage into aromatic benzyltoluenes at low temperatures to advance liquid organic hydrogen carrier technology. The hydrogenation activity of Ru/K/MgO catalysts exhibits a volcano-shaped dependence on the K content at the maximum with 0.02 wt%. This is in good agreement with the strength and capacity of H2 adsorption derived from basicity, despite a gradual decrease in the textural property and the corresponding increase in the Ru particle size with increasing the K content. Density functional theory calculations show that heterolytic hydrogen adsorption properties (strength and polarization) are facilitated up to a specific density of K on the Ru–MgO interface and excessive K suppresses heterolytic H2 adsorption by direct interaction between K and hydrogen, assuring the hydrogenation activity and H2 adsorption capability of Ru/K/MgO catalysts. Hence, the Ru/K/MgO catalyst, when K is added in an optimal amount, is highly effective to accelerate hydrogen storage kinetics at low temperatures owing to the enhanced heterolytic H2 adsorption.
Keywords: Benzyltoluene; Chemical hydrogen storage; Heterolytic H2 adsorption; Hydrogen carriers; Hydrogenation activity; Lows-temperatures; Organics; Potassium promotion; Ru–MgO interface; ]+ catalyst; Charge transfer; Chemical hydrogen storage; Heterolytic H2 adsorption; Potassium promotion; Ru–MgO interface; Supported Ru catalysts